Multiple roles of the extracellular vestibule amino acid residues in the function of the rat P2X4 receptor - Rokic, Milos B; Stojilkovic, Stanko S; Vavra, Vojtech; Kuzyk, Pavlo; Tvrdonova, Vendula; Zemkova, Hana (PloS one, 2013)
The binding of ATP to trimeric P2X receptors (P2XR) causes an enlargement of the receptor extracellular vestibule, leading to opening of the cation-selective transmembrane pore, but specific roles of vestibule amino acid residues in receptor activation have not been evaluated systematically. In this study, alanine or cysteine scanning mutagenesis of V47-V61 and F324-N338 sequences of rat P2X4R revealed that V49, Y54, Q55, F324, and G325 mutants were poorly responsive to ATP and trafficking was only affected by the V49 mutation. The Y54F and Y54W mutations, but not the Y54L mutation, rescued receptor function, suggesting that an aromatic residue is important at this position. Furthermore, the Y54A and Y54C receptor function was partially rescued by ivermectin, a positive allosteric modulator of P2X4R, suggesting a rightward shift in the potency of ATP to activate P2X4R. The Q55T, Q55N, Q55E, and Q55K mutations resulted in non-responsive receptors and only the Q55E mutant was ivermectin-sensitive. The F324L, F324Y, and F324W mutations also rescued receptor function partially or completely, ivermectin action on channel gating was preserved in all mutants, and changes in ATP responsiveness correlated with the hydrophobicity and side chain volume of the substituent. The G325P mutant had a normal response to ATP, suggesting that G325 is a flexible hinge. A topological analysis revealed that the G325 and F324 residues disrupt a β-sheet upon ATP binding. These results indicate multiple roles of the extracellular vestibule amino acid residues in the P2X4R function: the V49 residue is important for receptor trafficking to plasma membrane, the Y54 and Q55 residues play a critical role in channel gating and the F324 and G325 residues are critical for vestibule widening.
Keywords: Allosteric Regulation; Receptors, Purinergic P2X4; hydrofobní a hydrofilní interakce; purinergní receptory P2X4; Rats; transfekce; HEK293 Cells; Mutagenesis, Site-Directed; gating iontového kanálu; Amino Acids; Ivermectin; mutageneze cílená; Point Mutation; vztahy mezi strukturou a aktivitou; Transfection; molekulární modely; Models, Molecular; lidé; adenosintrifosfát; Ion Channel Gating; sekundární struktura proteinů; alosterická regulace; Patch-Clamp Techniques; Structure-Activity Relationship; Adenosine Triphosphate; Animals; Protein Structure, Secondary; HEK293 buňky; krysa rodu Rattus; metoda terčíkového zámku; Humans; aminokyseliny; bodová mutace; ivermektin; Hydrophobic and Hydrophilic Interactions; zvířata